The association of appendicular skeletal muscle mass with anthropometric, body composition, nutritional, inflammatory, and metabolic variables in non-dialysis-dependent chronic kidney disease men - Katarzyna Romejko; Katarzyna Szamotulska; Aleksandra Rymarz; Rozmyslowicz Tomasz; Stanisław Niemczyk (Frontiers in Medicine, 2024)
BackgroundMuscle atrophy affects more than 50% of patients with chronic kidney disease (CKD) and is associated with increased morbidity and mortality. It is crucial to understand the mechanisms involved in the muscle atrophy in CKD and search for specific determinants of skeletal muscle mass loss, especially those which are available in everyday medical practice. This study aimed to evaluate the association between appendicular skeletal muscle mass (ASM) and anthropometric, body composition, nutritional, inflammatory, metabolic, and kidney function variables in non-dialysis-dependent CKD men.MethodsA total of 85 men with CKD and eGFR lower than 60 mL/min/1.73 m2 were included in the cross-sectional study: 24 participants with eGFR 59–45 mL/min/1.73 m2, 32 individuals with eGFR 44–30 mL/min/1.73 m2, and 29 men with eGFR ≤29 mL/min/1.73 m2. ASM was estimated by bioimpedance spectroscopy (BIS) with the use of a Body Composition Monitor (BCM). To evaluate ASM from BCM, Lin’s algorithm was used. Among anthropometric parameters, height, weight, and body mass index (BMI) were measured. Serum laboratory measurements were grouped into kidney function, nutritional, inflammatory, and metabolic parameters.ResultsASM was significantly associated with anthropometric and body composition variables. According to the anthropometric parameters, ASM correlated positively with weight, height, and BMI (p < 0.001 and r = 0.913, p < 0.001 and r = 0.560, and p < 0.001 and r = 0.737, respectively). Among body composition variables, ASM correlated significantly and positively with lean tissue mass (LTM) (p < 0.001, r = 0.746), lean tissue index (LTI) (p < 0.001, r = 0.609), fat mass (p < 0.001, r = 0.489), and fat tissue index (FTI) (p < 0.001, r = 0.358). No other statistically significant correlation was found between ASM and kidney, nutritional, metabolic, and inflammatory variables.ConclusionIn male patients with CKD stages G3–G5 not treated with dialysis, ASM correlates significantly and positively with anthropometric and body composition parameters such as weight, height, BMI, LTM, LTI, fat mass, and FTI. We did not observe such relationship between ASM and kidney function, nutritional, metabolic, and inflammatory variables.